Identity-based fully homomorphic encryption from learning with error problem - Yan GUANG; Yue-fei ZHU; Jin-long FEI; Chun-xiang GU; Yong-hui ZHENG (Tongxin xuebao)
The fully homomorphic encryption schemes based on learning with errors problem own a great potential value in the cloud computing security. However, the existing schemes share a common flaw of large sized public keys, which may cause inefficiency of such schemes in the key and identity management. An identity-based fully homomorphic en-cryption scheme was presented. The scheme compromises the merits of both identity-based and fully homomorphic en-cryption schemes, and it overcomes the above mentioned flaw. The security of the proposed scheme reduces to the hard-ness of learning with errors problem and the one-wayness of trapdoor function in the random oracle model.